Measuring intellectual capital and its impact on financial performance by improving the profitability of Iraqi commercial banks - A’abayes Talal, Nahla; Greedi Hamdan, Wissam (Iraqi Journal for Administrative Sciences, 2024)
The research aims to measure the impact of intellectual capital on financial performance in improving the profitability of Iraqi commercial banks by answering the following main question: What is the impact of intellectual capital on the profitability of Iraqi commercial banks listed in the stock market? To achieve the objectives of the research, the two researchers prepared a questionnaire, a copy of which is attached with the research, and distributed electronically, and in a random sampling method to Iraqi commercial banks, and the number of answers reached 105, analyzed using the spss program according to the objective and hypothesis of the research The research concluded a set of conclusions, the most important of which is the interest in intellectual capital because of its impact on improving production, increasing the creative capabilities of employees, maintaining customers and attracting new ones. Competitiveness is considered the basis for building and progressing economies, as it is no less valuable than physical assets. Human capital is the most important component of intellectual capital, since customers are the source of revenue for the economic unit.1. The research aims to measure the impact of intellectual capital on financial performance in improving the profitability of Iraqi commercial banks by answering the following main question: What is the impact of intellectual capital on the profitability of Iraqi commercial banks listed in the stock market?